Connective professionalism: Towards (yet another) ideal type. Issue 2 (26th July 2020) - Adams, Tracey L; Clegg, Stewart; Eyal, Gil; Reed, Mike; Saks, Mike
ABSTRACT: In this essay, four leading scholars provide critical commentary on an article entitled 'Protective or Connective Professionalism? How Connected Professionals Can (Still) Act as Autonomous and Authoritative Experts' (Noordegraaf, 2020, Journal of Professions and Organization, 7/2). Of central concern to all four commentators is Noordegraaf's use of ideal types as a heuristic device to make his case and capture historical change over time. While some question the usefulness of ideal types, others question Noordegraaf's use of them. The commentators raise additional concerns, especially the limited attention to variations across professions, geographic regions, and limited attention to social–historical contexts.